Efeito da dieta hipoprotéica-hiperglicídica sobre a sensibilidade à insulina e a gliconeogênese hepática em ratos na fase de crescimento - Pereira, Mayara Peron (2012)
Previous studies from our laboratory found that growing rats submitted to low-protein, high-carbohydrate (LPHC) diet have lower fasting glucose (15h), when compared to animals treated with control diet (C), even with impaired insulin signaling in adipose tissues. Given the above, the objective of this study was evaluate hepatic gluconeogenesis and insulin sensitivity in male Wistar rats (~100g) underwent LPHC or C diet for 15 days. After this period the animals were fasted for 15 h, when they were used for the insulin tolerance test (ITT), glucose tolerance test (GTT), blood dosages, liver perfusion in situ, in vitro incorporation of 14C-pyruvate and levels protein liver of phosphoenolpyruvate carboxykinase (PEPCK) and glycerokinase (GyK). Data are expressed as mean ± SEM (Student t-test, P<.05). Investigations of the hepatic gluconeogenesis show that the LPHC group showed increase in plasma concentrations of gluconeogenic substrates: glycerol (65%), L-lactate (122%), L-glutamine (25%) and L-alanine (65%) when compared to C group. The increased concentration of L-lactate suggests an increase in glucose anaerobic by the tissues. The liver production of glucose (AUC-µmol.g-1 ) from saturating concentrations of glycerol (1mM), pyruvate (5mM) and L-glutamine (5mM), measured by in situ liver perfusion, (using a substrate each time), was higher in LPHC group (1.04 ± 0.10; 0.84 ± 0.05; 0.60 ± 0.01, respectively) when compared with C group (0.67 ± 0.40; 0.68 ± 0.05; 0.39 ± 0.04, respectively). Serum concentrations of L-lactate and glycerol in LPHC group were close to the concentrations required to produce maximum glucose. The protein levels of PEPCK in LPHC group was higher (25%) compared to C group and the GyK was not altered by diet. The incorporation of 14C-pyruvate (nmol.g-1 .h-1 ) in LPHC group was higher in glucose (LPHC- 569.2 ± 30.72 and C- 463.0 ± 18.71), and lowest in glycerol (LPHC17.98 ± 2.23 and C- 24.10 ± 1.63), and both groups incorporation was higher in glucose and lower in glycerol. The LPHC animals also showed higher (AUC-mg.dL-1 .120 min-1 : 18,520 ± 513.8) glucose tolerance and more rapid decline (Kitt: 0.039 ± 0.002) of plasma glucose by insulin administration, compared to C animals (AUC-mg.dL-1 .120 min-1 : 23,679 ± 614.5; Kitt: 0.030 ± 0.002, respectively). We conclude that adaptation to LPHC diet, increased capacity for hepatic gluconeogenesis. Moreover, glycerol and Llactate are the main physiological substrates that permit the maintenance of blood glucose, even with the increase in glucose utilization.